LIBERALISME DALAM PENDIDIKAN ISLAM: TANTANGAN DAN IMPLIKASINYA TERHADAP MANAJEMEN PENDIDIKAN ISLAM KONTEMPORER - Repi Arianto; Didi Kosmanto; Wawan Herianto; Lukman Asha; Ifnaldi; Hajja , Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Liberalism is one of the important issues in contemporary Islamic education, emphasizing freedom of thought, rationality, and intellectual openness. This study aims to analyze liberalism in Islamic education and its implications for contemporary Islamic educational management. The study employed a qualitative method using a library research approach through the review of relevant scientific literature. Data were analyzed using descriptive content analysis. The findings indicate that liberalism can promote the development of academic culture, critical thinking skills, learning innovation, and the integration of religious and modern scientific knowledge. However, liberalism also presents challenges, including the potential for value relativism and the need to maintain Islamic identity within the educational process. Therefore, Islamic educational management should integrate academic freedom with Islamic values in a balanced manner to respond to contemporary challenges without losing the fundamental goals of Islamic education.